Measuring The Readiness Of Slaughterhouses As A Strategic Upstream Strengthening Halal Certification In East Java - Hikmatul Hasanah; Siti Alfiyah; Moh Ali Syaifudin Zuhri; Roni Subhan (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
East Java as a national food center must receive serious attention regarding the existence of slaughterhouses that meet halal and hygiene standards. If the RPH as an upstream halal product can be improved, then the downstream area will be greatly helped in realizing a product ready for consumption and use. And ultimately, halal certification for processed meat food products will be achieved faster and better. Based on field phenomena, there are still many processed meat food products that do not yet have halal certification, this is where the upstream slaughterhouse war becomes very urgent. From research using a qualitative approach and this type of library research (Library Research), data was obtained from previous research, news portals, and websites that provide information about the readiness of RPH as a strategic upstream for strengthening halal certification in East Java, which then resulted in the conclusion that the readiness of RPH in East Java is still relatively low. Hence, there is a need for synergistic cooperation between the relevant parties, namely: the community, SMEs, RPH, and government.